John Luther Adams Across the Distance, Meltdown Festival, Royal Festival Hall, London. (7th December 2015) - Graham, Cameron
Abstract : John Luther Adams holds a unique position in American contemporary music. His works are as tinged with minimalist virtues as they are rigorously experimental, offering sound worlds that seem at once unearthly and welcoming, unconventional yet accessible. At the core of the Pulitzer Prize-winning composer's work lies a major concern with translating the tenuous and illusory concept of acoustic and natural sonic space into densely textured instrumental works. Exploring the composer's oeuvre, one senses a deep fascination with acoustic phenomena; in works such as the orchestral soundscape Becoming Ocean (2012), and the percussion pieces Inuksuit (2009) and Strange and Sacred Noise (1997), the composer eschews any audible rhythmic and melodic complexities in favour of serene yet coursing sound masses and highly sonorous ensemble textures.